All-optical generation and photoassociative probing of sodium Bose–Einstein condensates - Johanning, M. (2014)
We demonstrate an all-optical technique to evaporatively produce sodium Bose–Einstein condensates (BEC). We use a crossed-dipole trap formed from light near 1 μm, and a simple ramp of the intensity to force evaporation. In addition, we introduce photoassociation as diagnostic of the trap loading process, and show that it can be used to detect the onset of BEC. Finally, we demonstrate the straightforward production of multiple traps with condensates using this technique, and that some control over the spinor state of the BEC is achieved by positioning the trap as well.